Managing project success using project risk and green supply chain management - Fernando, Yudi; Walters, Tim; Mohamad Norris, Ismail; Seo, Yong Won; Kaimasu, Masatoshi (Emerald Publishing Limited, 2018)
Purpose: The implementation of the risk management in the development of new car models can contribute to the improvement of the project management performance and project success. The purpose of this paper is to provide evidence about whether project risk management (PRM) and green supply chain management (GSCM) are positively related to project management performance and the project success. Design/methodology/approach: Data were collected from 145 project managers in the Malaysian automobile manufacturing industry and analyzed using structural equation modeling. Findings: The results found that PRM and the GSCM had a positive association with project management performance and the project success.